Ecological aspects of site recovery under swidden-fallow management in the Peruvian Amazon - Unruh, Jon D. (1988)
The ecological importance of fallowing to swidden (slash and burn) agriculture is well known. Cyclic agroforestry systems which emphasize utilization of the fallow cycle should, where appropriate, consider the ecologic processess of site recovery, so as not to impair the productivity of the subsequent swidden cycle. this artical discusses the ecologic ?fit? of a cyclic swidden-fallow management scheme into swidden cultivation and fallow succession. Such a fit suggests a reciprocally reinforcing situation between this agroforestry design and processes involved in site recovery. Observed among some indigenous and colonist inhabitants of the Peruvian Amazon, this system produces fallow crops and products, while enhancing site nutrient recovery. The economic benefits of this scheme have recently been reported (Denevan and Padoch, n.d.) while the ecologic attributes involved in promoting site recovery have not; primarily these include: a)Less destruction of the nutrient cycling root-mat in the swidden cycle, and its quicker re-formation in the fallow cycle. b)Discouraging the establishment of exotic, pantropical weeds and grasses such as imperata, while encouraging the colonization of local, early successional species. c)Encouraging the earlier establishment of woody plants in abandoned swiddens. d)A natural litterfall higher in nutrients than in unmanaged fallows. e)Additions of ?slash? litterfall higher in nutrient content than natural litterfall in the proximity of valuable managed plants. f)The increased capacity of the managed stand to scavenge limiting nutrients such as N and P from, and leach unneeded quantities of non-limiting nutrients such as K, Ca and Mg to, thoughfall. g)Increasing the alkalinity of throughfall, possibly resulting in less soil cation leaching in managed fallows. h)Staggering seed production, germination and maturation times of the rapid nutrient sycling softwood trees. i)Increasing the spontaneously occuring abundance of valuable fallow plants with management of successive fallow cycles, thereby possibly reducing the labor requirement, and increasing the value of this agroforestry scheme over time.